Pengaruh Ewom Terhadap Purchase Intention - Bangun, Muhammad Fathurrahman; Ismail, Taufiq (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2024)
This study aims to determine how Electric Word of Mouth influences Purchase intention for Kahf products on the TikTok application among Generation Z in Malang City. This type of research is explanatory research, which explains or proves the relationship between independent and dependent variables. This study uses a sample of 242 respondents, with questionnaires distributed online through Google Forms. The sampling method used is non-probability sampling with a purposive sampling technique. The sample consists of respondents who are Generation Z in Malang City. Data analysis employs PLS-SEM analysis using SmartPLS 4.0. The results show that the Information adoption variable positively and significantly influences the Purchase intention variable, the Information usefulness variable positively and significantly influences the Information adoption variable, the Information quality variable positively and significantly influences the Information usefulness variable, the Information credibility variable positively and significantly influences the Information usefulness variable, and the Information quantity variable also positively and significantly influences the Information usefulness variable. Abstrak Penelitian ini bertujuan untuk mengetahui bagaimana pengaruh Electric Word of Mouth terhadap Purchase intention produk Kahf di aplikasi TikTok pada Generasi Z di Kota Malang. Jenis penelitian ini adalah explanatory research yang menjelaskan atau membuktikan hubungan pengaruh antar variabel independen dan dependen. Penelitian ini menggunakan sampel sebanyak 242 responden yang mana penyebaran kuesioner dilakukan melalui Google formulir secara online. Pengambilan sampel menggunakan metode non-probability sampling dengan teknik purposive sampling. Sampel terdiri dari responden yang merupakan Generasi Z yang ada di Kota Malang. Analisis data menggunakan Analisis PLS-SEM dengan menggunakan SmartPLS 4.0. Hasil penelitian menunjukan bahwa variabel Information adoption secara positif dan signifikan memengaruhi variabel Purchase intention, variabel Information usefulness secara positif dan signifikan memengaruhi variabel Information adoption, variabel Information quality secara positif dan signifikan memengaruhi variabel Information usefulness, variabel Information credibility secara positif dan signifikan memengaruhi variabel Information usefulness dan variabel Information quantity juga secara positif dan signifikan memengaruhi variabel Information usefulness.